Implementasi Sistem Informasi Manajemen Pendidikan (Simdik) Dalam Meningkatkan Mutu Pendidikan Di Madrasah Aliyah Negeri Di Kabupaten Tanjung Jabung Barat Provinsi Jambi In Pondok Pesantren - Ahmad Ridwan (Proceedings of Annual Conference on Islamic Educational Management, 2021)
This study describes the implementation of an education management information system in improving the quality of MAN education in Tanjung Jabung Barat Regency, Jambi Province. The Education Management Information System was developed to meet the needs of madrasah/school institutions, where schools require the management of computerized academic activities as a contribution to improving the quality of madrasah/school services as well as in order to facilitate and expedite the teaching and learning process of schools and school services. This study uses a qualitative approach by using observation, interviews, and documentation as data collection techniques. The results of this study indicate that the implementation of an education management information system at MAN in Tanjung Jabung Barat Regency, Jmabi Province is in the form of utilizing an application system consisting of teaching and educational staff services by empowering the SIMPATIKA application (Information System for Educators and Education Personnel of the Ministry of Religion), e-learning applications. -learning, BNI eduPATROL application, fingerprint application for both teachers and students and web-based application for new student admissions (PPDB). There are several supporting and inhibiting factors in the implementation of SIMDIK at MAN in Tanjung Jaung Barat Regency, Jambi Province, namely the availability of information system facilities and obstacles in human resources and technical errors as well as student obstacles in participating in learning with the application.